CHARACTERISTICS, COMPONENTS, AND STRUCTURE OF MANAGEMENT INFORMATION IN EDUCATIONAL INSTITUTIONS - Revanti Atlantika Prayugo (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2022)
Management Information Systems is a field of study that is currently growing rapidly in line with the development of the business world and advances in information technology as a support for business activities. The increasing complexity of systems and their roles in various fields of life requires the study of Management Information Systems through a sociotechnical approach. Until now, discussions and debates about information systems still often revolve around general assumptions that lead to the understanding that information systems are solely related to technical approaches. A multiperspective view of information systems shows that they are a multidisciplinary field of study. This strengthens the position of Management Information Systems, supported by information technology, in shaping enterprise systems and playing a role in enhancing the value chain of a company or organization. This research employs a literature study method to analyze the characteristics, components, and structure of management information in educational institutions. The findings indicate that by utilizing management information systems, educational institutions can improve transparency, accountability, and the quality of education.